Hubungan Kepribadian Guru dengan Sikap Siswa dalam Proses Pembelajaran - Thomson Siallagan; Jamli Barus (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2023)
AbstractEducation as "a conscious, systematic and continuous effort to transmit, generate or acquire either knowledge, attitudes, values, skills, or sensibilities, or any result of such an effort. A person's personality is the work of the Holy Spirit through the Word that we preach or proclaim; through the Gospel that we establish as the center of faith, we 'give birth' to them through the power of the Gospel and the Word by the Holy Spirit in the power of God. Then as the end goal of Christian education, they have the personality or character of Christ. The personality of a lecturer can basically be seen from his actions, speech, the way he associates, the way he dresses and the way he deals with every problem or issue he faces. Lecturers are professional educators who are tasked with developing the personality of students or now better known as student character. Adequate mastery of the personality competence of a lecturer will greatly help efforts to develop the character of his students. By presenting as a figure who can be di-gugu (trusted) and imitated. Psychologically, children tend to feel confident in what the teacher is teaching. Keywords: personality, student behaviour  AbstrakPendidikan sebagai sebuah usaha sadar, sistematis dan berkesinambungan untuk menyalurkan, menghasilkan atau memperoleh pengetahuan, sikap, nilai, keterampilan atau kepekaan, serta segala sesuatu yang dihasilkan dari usaha tersebut. Kepribadian seseorang adalah karya Roh Kudus melalui Firman yang kita beritakan atau beritakan; melalui Injil yang kita tetapkan sebagai pusat iman, kita "melahirkan" mereka dengan kuasa Injil dan Firman melalui Roh Kudus dalam kuasa Allah. Kemudian, sebagai tujuan akhir dari pendidikan Kristen, mereka memiliki kepribadian atau karakter Kristus. Kepribadian seorang dosen pada dasarnya dapat dilihat dari tindakannya, tutur katanya, cara bergaulnya, cara berpakaiannya dan cara menyikapi setiap masalah atau persoalan yang dihadapinya. Dosen adalah pendidik profesional yang dibebani tugas untuk mengembangkan kepribadian mahasiswa, atau yang lebih dikenal dengan karakter mahasiswa. Penguasaan kompetensi kepribadian yang memadai dari seorang dosen akan sangat membantu upayanya dalam mengembangkan karakter mahasiswanya. Dengan menampilkan dirinya sebagai sosok yang dapat di-gugu (dipercaya) dan ditiru. Secara psikologis, anak cenderung mempercayai apa yang diajarkan oleh gurunya. Kata Kunci: kepribadian, sikap siswa